Portfolio-Analysis Methods for Assessing Capability Options - Davis, Paul K. (RAND Corporation, 2008)
An analytical framework and methodology for capability-area reviews is described, along with new tools to support capabilities analysis and strategic-level defense planning in the Defense Department and the Services. BCOT generates and screens preliminary options, and the Portfolio-Analysis Tool (PAT) is used to evaluate options that pass screening. The concepts are illustrated with applications to Global Strike and Ballistic Missile Defense. Recommendations are made for further defense-planning research.